High-throughput sequencing analysis of genes encoding the B-lymphocyte receptor heavy-chain CDR3 in renal and peripheral blood of IgA nephropathy. Issue 10 (15th October 2019) - Chen, Dapeng; Zhang, Zheng; Yang, Yue; Hong, Quan; Li, Wenge; Zhuo, Li
Abstract: Aim: IgA nephropathy (IgAN) is one of the most common chronic glomerulonephritis. Its etiology and pathogenesis remain unclear. We thus explored the immune repertoire of the B-cell receptor (BCR) and the heavy-chain complementarity-determining region 3 (CDR3) in renal tissue and peripheral blood of IgAN patients. Method : Total RNAs extracted from renal tissues and peripheral blood of patients and peripheral blood of healthy controls (HCs) were analyzed via high-throughput multiplex PCR sequencing. We amplified and sequenced BCR heavy-chain CDR3 regions to explore repertoire diversity, V/J gene family distribution, CDR3 lengths, BCR heavy-chain variants, consistency between tissue and peripheral blood data, and clones 'shared' by these bodily compartments. Results: We identified the renal tissue and peripheral blood BCR heavy-chain CDR3 immune repertoires of 15 IgAN patients. Top1 could be more readily cloned from peripheral blood of patients than from controls ( P<0.05 ), the average CDR3 length was significantly shorter in patients than in HCs ( P<0.05 ), the variant frequency of the gene encoding the BCR heavy chain was higher in patients than in HCs ( P<0.05 ), and the BCR variant frequency was highest in IgAN kidney tissue. Preliminary screening for 'shared' clones showed that, in at least 13 patients, the 'ALYFHNSAY', 'ARWGPMYYYMDV', 'ARDQGALNA', and 'ARVDNPADF' CDR3 sequences were evident in peripheral blood samples from patients, but not HCs. Conclusions: We found that the 'ALYFHNSAY', 'ARWGPMYYYMDV', 'ARDQGALNA', and 'ARVDNPADF' clonal sequences may be useful for noninvasive diagnosis and treatment planning in IgAN.